International workshop on methodological evolution to improve estimates of life history parameters and fisheries management of data-poor deep-water snappers and groupers. (October 2015) - Newman, Stephen J.; Wakefield, Corey B.; Williams, Ashley J.; O'Malley, Joseph M.; Nicol, Simon J.; DeMartini, Edward E.; Halafihi, Tuikolongahau; Kaltavara, Jeremie; Humphreys, Robert L.; Taylor, Brett M.; Andrews, Allen H.; Nichols, Ryan S.
Abstract: Knowledge of both the life history characteristics and catch and effort statistics of exploited deep-water fishes such as snappers and groupers is typically limited. This contributes to increased uncertainty in stock assessments and, depending on the diligence in governance, is more likely to result in either highly conservative or unsustainable management arrangements. Developments, challenges and advances in the methods for obtaining life history data for these species were discussed at a workshop in May 2015. The key points raised included nascent methods for otolith sectioning and interpretation, the need for standardised international ageing protocols and the issues and challenges in characterising reproductive maturation, including during non-spawning months due to resource limitations. Strategic research directions are identified to address knowledge gaps and thus better inform fisheries management.